A NEW GENUS PROTRELLIMA OF SUBFAMILY PROTRELLODINAE (THELASTOMATIDAE : OXYUROIDEA) FROM MANIPUR - GAMBHIR, R.K.; CHINGLENKHOMBA, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
A new genus of Thelastomatidae viz. Protrellima gen, nov. is described from Manipur and its affinities are discussed. The genus belongs to the subfamily Protrelloidinae.